In Pursuit of Greatness: CEO Narcissism, Entrepreneurial Orientation, and Firm Performance Variance - Wales, William J.; Patel, Pankaj C.; Lumpkin, G. T. (Journal of Management Studies, 2013)
AbstractBuilding upon the perspective that narcissism is a leadership trait with both ‘bright’ and ‘dark’ sides, the present study examines the question of whether companies led by narcissistic CEOs exhibit higher levels of entrepreneurial orientation (EO). Moreover, this research examines whether EO partially explains why narcissistic CEO‐led firms experience greater variability in firm performance. Using survey data collected from 173 CEOs, and an archival measure of firm performance variance, we find support for our model. These findings offer an improved understanding of how CEO narcissism influences performance variance, and why the firms they lead may even, at times, be viewed as on a path to success. Study implications are discussed.